ANALISIS PENGALAMAN PRA KOMITE AUDIT TERHADAP PENDETEKSIAN KECURANGAN PELAPORAN KEUANGAN - Sekar Niken Kartika; Sudarno Sudarno (Diponegoro Journal of Accounting, 2014)
This research attempt to  assure  that the experience of pre committee audit can be more easily detect  fraudulent  financial reporting.. This  study  used  secondary  data  taken  from  annual report BAPEPAM for year 2008, 2009, 2010, 2011, 2012 and the companies list that investigated from pasal 69 and regulation number VIII.G.7 from annual report  BAPEPAM in the same year.This study used amount of data to be analyzed as many as 50 companies consisting of 25 companies that conduct fraud and 25 non-fraud companies. Using purposive sampling method, data analysis includes descriptive statistic, multikolinieritas and logistic regression.  Analyzing data using IBM SPSS16 software.Based on the survey results revealed that pre committee audit experience affect financial reporting fraud detection with a significance of 0.094.